Philo of Alexandria : an annotated bibliography, 1987-1996 : with addenda for 1937-1986 - Runia, David T. (Vigiliae Christianae, Supplements, 2000)
This volume is a continuation of Philo of Alexandria: an Annotated Bibliography 1937-1986, published by Roberto Radice and David Runia in 1988 (second edition 1992). Prepared with the collaboration of the International Philo Bibliography Project, it contains a complete listing of all scholarly writings on Philo in all languages for the period 1987 to 1996. Part One lists texts, translations, commentaries et cetera (75 items). Part Two contains critical studies (880 items). In part Three additional works for the years 1937-1986 are presented (170 items). In all cases a brief description of the contents of the contribution is given. Seven indices, including a detailed Index of subjects, complete the work.